2016
DOI: 10.1039/c6dt00847j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the structure and solubility of nanojars by peripheral ligand substitution, leading to unprecedented liquid–liquid extraction of the carbonate ion from water into aliphatic solvents

Abstract: Nanojars, a novel class of neutral anion-incarcerating agents of the general formula [Cu(II)(OH)(pz)]n (Cun; n = 27-31, pz = pyrazolate anion), efficiently sequester various oxoanions with large hydration energies from water. In this work, we explore whether substituents on the pyrazole ligand interfere with nanojar formation, and whether appropriate substituents could be employed to tune the solubility of nanojars in solvents of interest, such as long-chain aliphatic hydrocarbons (solvent of choice for large-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 49 publications
(66 reference statements)
2
43
0
Order By: Relevance
“…A unique class of copper-pyrazolate complexes is defined by nanojars, based on a series of cyclic polymerization isomers, [cis-Cu II (-OH)(-pz)] n (pz = pyrazolate anion, n = 6-14, except 11), which incarcerate anions with large hydration energies (e.g., sulfate, phosphate, carbonate) with unprecedented strength (Fernando et al, 2012;Mezei, 2015;Ahmed, ISSN 2056-9890 Szymczyna et al, 2016) and permits the extraction of such anions from water into aliphatic solvents (Ahmed, Calco et al, 2016). Nanojars are obtained by self-assembly from a copper salt, pyrazole and a base (needed both for deprotonating pyrazole and as a hydroxide ion source) in the presence of an anion with large hydration energy, via a trinuclear intermediate, which is isolable and can be converted into nanojars by adding a base .…”
Section: Chemical Contextmentioning
confidence: 99%
“…A unique class of copper-pyrazolate complexes is defined by nanojars, based on a series of cyclic polymerization isomers, [cis-Cu II (-OH)(-pz)] n (pz = pyrazolate anion, n = 6-14, except 11), which incarcerate anions with large hydration energies (e.g., sulfate, phosphate, carbonate) with unprecedented strength (Fernando et al, 2012;Mezei, 2015;Ahmed, ISSN 2056-9890 Szymczyna et al, 2016) and permits the extraction of such anions from water into aliphatic solvents (Ahmed, Calco et al, 2016). Nanojars are obtained by self-assembly from a copper salt, pyrazole and a base (needed both for deprotonating pyrazole and as a hydroxide ion source) in the presence of an anion with large hydration energy, via a trinuclear intermediate, which is isolable and can be converted into nanojars by adding a base .…”
Section: Chemical Contextmentioning
confidence: 99%
“…Nanojars, supramolecular coordination complexes of the formula [{Cu(-OH)(-pz)} n anion] (pz = pyrazolate anion; n = 27-36), have emerged as a new class of anion encapsulation agents of unparalleled efficiency, which allow the extraction of anions with large hydration energies, such as phosphate, carbonate and sulfate, from water into organic solvents (Mezei, Baran et al, 2004;Fernando et al, 2012;Mezei, 2015;Ahmed, Szymczyna et al, 2016;Ahmed, Calco & Mezei, 2016;Ahmed, Hartman & Mezei, 2016). Trinuclear copper pyrazolate complexes have been identified as key intermediates in the self-assembly mechanism of nanojars from copper(II) nitrate, pyrazole and NaOH (1:1:2 molar ratio) in the presence of carbonate .…”
Section: Chemical Contextmentioning
confidence: 99%
“…New evidence supporting the vulnerability of nanojars to acids emerges from an unexpected source. An attempt to grow single crystals from a solution of (Bu 4 N) 2 [{Cu(-OH)(-4-Ipz)} n CO 3 ] (n = 27-31) (Ahmed, Calco et al, 2016) in chloroform/1,4-dioxane provided, instead of the expected nanojars, crystals of (Bu 4 N) 2 [Cu 3 ( 3 -Cl) 2 (-4-I-pz) 3 Cl 3 ]Á0.5dioxane , accompanied by a color change of the solution from blue to green. The chloride ions originating from CHCl 3 is not surprising, as chloroform has long been known to slowly decompose in the presence of air and moisture producing HCl and phosgene (CHCl 3 + 1 2 O 2 !…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an aqueous Ba 2+ solution is unable to precipitate the corresponding barium salt (e.g., BaSO 4 , K sp = 1.08 × 10 −10 at 25 °C in H 2 O) when stirred with a solution of the nanojars. We have also demonstrated that nanojars are able to transfer these anions, including one of the most hydrophilic ones, carbonate, from water into aliphatic solvents [ 11 ]. Thus, nanojars can be used as extraction agents for the removal of such anions from contaminated aqueous media by liquid–liquid extraction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%